Case-based Clinical Reasoning Competitions: A Novel Method to Teach and Assess Clinical Reasoning Skills Among Gastroenterologists - Sadeghi, Anahita; Adibi, Peyman; Önder, Fatih Oğuz; Değertekin, Bülent; Turan, Dilara; Bor, Serhat (Turkish Journal of Gastroenterology, 2024)
Cite this article as: Sadeghi A, Adib P, Oğuz Önder F, Değertekin B, Turan D, Bor S. Case-based clinical reasoning competitions: a novel method to teach and assess clinical reasoning skills among gastroenterologists. Turk J Gastroenterol. 2024;35(10):805-807.